The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.0742-2822.2005.03153.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Atrial Septal Defect Size with 3D‐Transesophageal Echocardiography: Comparison with Balloon Method

Abstract: Three-dimensional transesophageal echocardiography and transcatheter methods are two complementary techniques for the success of transcatheter ASDs closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 23 publications
(40 reference statements)
1
19
1
Order By: Relevance
“…[11] Recently, 3D TEE has been used to aid selection of device size. [25] There is good correlation between 3D TEE measurement of maximal diameter and SBD in patients with a single ASD.…”
Section: Discussionmentioning
confidence: 98%
“…[11] Recently, 3D TEE has been used to aid selection of device size. [25] There is good correlation between 3D TEE measurement of maximal diameter and SBD in patients with a single ASD.…”
Section: Discussionmentioning
confidence: 98%
“…Implanting too large a device may lead to a mushrooming deformity or cardiac perforation or it may increase the risk of device erosion over time,8-10 while using too small a device has been accompanied by device instability, distal embolisation of the device, and residual shunting 11,12. Balloon sizing of the defect has been considered the gold standard for measuring ASD size,13-18 while angiography, transthoracic echocardiography (TTE), two- and three-dimensional transoesophageal echocardiography (TEE), intracardiac echocardiography, and intravascular ultrasound have been tried as guiding methods during the closure procedure 10,14-16,18-20…”
Section: Introductionmentioning
confidence: 99%
“…Previous 3D studies have described the dynamic nature of the atrial defect size during the cardiac cycle [9][10][11]. Studies have also demonstrated that the defect size determined by 3DTEE correlates well with the balloon sizing method [6,12]. However, these studies have been performed using gated-acquisition methods, which require lengthy acquisitions and tedious off-line reconstructions.…”
Section: Introductionmentioning
confidence: 99%